Regression analysis to evaluate the impact of information technologies tools on the performance of banks in Nigeria: English - Ajao, Olutunde; Ayenigba , Alfred Ayo; Aborisade , Johnson Funsho (CV. ARGA FARMA, 2024)
Commercial banking in Nigeria has experienced immense growth since the turn of the century. This growth is largely attributed to the increased use of information technology in banking operations. Banks in Nigeria have now adopted IT systems to better manage customer data, processing financial transactions, and providing customers with better access to banking services. Linear Regression analysis was carried out to determine the effect of the independent variable on the dependent variables. The t, F and Durbin Watson statistic tests were also carried out to determine the individual significance, overall joint significance and goodness of fit of the model respectively. The regression results indicated that there was a positive and significant relationship between profitability and customer independent technology. The results also revealed ATMs, POS, MMO, and IBT were a key determinant of banks performance. For example, banks in Nigeria can now offer customers online banking services, which make it easier for customers to access their accounts and transfer money. Banks can also benefit from IT systems to increase efficiency in processing transactions. This allows banks to reduce their costs and increase their profits .Overall, the adoption of IT in Nigerian banks has had a positive effect on their performance. The use of IT has allowed banks to increase their efficiencies, improve customer service, and increase their profitability.